Research on Optimal Energy Flow Calculation of an Electro-Thermal Coupled System via an Interior-Point Approach - Li, Zhaoying; Zhao, Yan; Xu, Jian; Shao, Qianzhi (Frontiers in Energy Research, 2022)
With the contradiction between energy consumption and ecological protection becoming increasingly prominent, it has become a serious issue to study an energy system with high efficiency, low pollution, and strong controllability. The application of the backpressure unit and the peak-shaving electric boiler makes the power grid and the heat grid connected and becomes an electro-thermal coupling system, which can be studied as a representative of the integrated energy system. In this study, to make full use of energy, a power system model considering a large number of distributed energy injections and a multi-source thermal system model are constructed. After the energy flow is solved, the optimization method of the electrothermal coupled system is studied to minimize the fuel consumption and obtain the minimum operating cost. In addition, a more comprehensive algorithm is proposed in this study, and the actual model is used in the fourth section of the article to verify that the algorithm can be practically applied.